KEKUATAN EKONOMI-POLITIK CHINA PASCA COVID-19 - Saragih, Hendra; Rahayu, Hanna; Zulham, Muhammad (Dauliyah: Journal of Islam and International Affairs, 2022)
The emergence of a new virus in China known as Covid-19 has resulted in it's spreading around the world. This has caused the WHO to declare the coronavirus as an epidemic and the world is now in a global health emergency situation as the international new cases increase day by day. Several countries have adopted the lockdown policy even though this has had major implications on various aspects of human life and on politics, industry, education, tourism and of course negative effects on the economy of each of these countries. At the beginning of the epidemic all citizens were told to stay home and the government closed all public activities. China is known as one of the greatest world economy, but the economy there is also affected. Due to coronavirus outbreak, china’s economic has dropped. This journal will describe the evolution of China's political economic in the near future facing Covid 19s in the perspective of ecomony-politic, Theory of interdependence and also the concept of cooperation.